A pragmatic randomized clinical trial of insulin glargine 300 U/mL vs first‐generation basal insulin analogues in insulin‐naïve adults with type 2 diabetes: 6‐month outcomes of the ACHIEVE Control study. Issue 11 (3rd September 2020) - Meneghini, Luigi F.; Sullivan, Sean D.; Oster, Gerry; Busch, Robert; Cali, Anna M. G.; Dauchy, Arnaud; Gill, Jasvinder; Bailey, Timothy S.
Abstract: Aims: To compare the safety and efficacy of insulin glargine 300 U/mL (Gla‐300) versus first‐generation standard‐of‐care basal insulin analogues (SOC‐BI; insulin glargine 100 U/mL or insulin detemir) at 6 months. Methods: In the 12‐month, open‐label, multicentre, randomized, pragmatic ACHIEVE Control trial, insulin‐naïve adults with type 2 diabetes (T2D) and glycated haemoglobin (HbA1c) 64 to 97 mmol/mol (8.0%–11.0%) after ≥1 year of treatment with ≥2 diabetes medications were randomized to Gla‐300 or SOC‐BI. The composite primary endpoint, evaluated at 6 months, was the proportion of participants achieving individualized HbA1c targets per Healthcare Effectiveness Data and Information Set (HEDIS) criteria without documented symptomatic (blood glucose ≤3.9 mmol/L [≤70 mg/dL]) or severe hypoglycaemia at any time of the day at 6 months. Results: Of 1651 and 1653 participants randomized to Gla‐300 and SOC‐BI, respectively, 31.3% and 27.9% achieved the composite primary endpoint at 6 months (odds ratio [OR] 1.19, 95% confidence interval [CI] 1.01–1.39; P = 0.03 for superiority); 78.4% and 75.3% had no documented symptomatic or severe hypoglycaemia (OR 1.19, 95% CI 1.01–1.41). Changes from baseline to month 6 in HbA1c, fasting plasma glucose, weight, and BI analogue dose were similar between groups. Conclusions: Among insulin‐naïve adults with poorly controlled T2D, Gla‐300 was associated with a statistically significantly higher proportion of participants achieving individualized HEDIS HbA1c targets without documented symptomatic or severe hypoglycaemia (vs SOC‐BI) in a real‐life population managed in a usual‐care setting. The ACHIEVE Control study results add value to treatment decisions and options for patients, healthcare providers, payers and decision makers.